TINJAUAN FIQH SIYASAH TERHADAP PENGELOLAAN PASAR TRADISIONAL MINASA MAUPA KABUPATEN GOWA - Bahar, Firdawati; Alimuddin, Alimuddin; Mustafa, Adriana (Siyasatuna: Jurnal Ilmiah Mahasiswa Siyasah Syar'iyyah, 2022)
As a public facility, the Minasa Maupa traditional market has a role in shaping and controlling the socio-economic conditions of the surrounding community. This study aims to find out how the fiqh siyasah review of the efforts to manage the Minasa Maupa Market by the Gowa Regency Government. This type of research is qualitative research with a syar'i and empirical juridical approach, data sources are obtained through primary data and secondary data. The management policy of the Minasa Maupa Traditional Market by the Gowa Regency Government is based on Regional Regulation Number 6 of 2016, although the fact is that it has not been carried out optimally, such as the lack of supporting facilities and cleanliness. In the review of fiqh siyasah, the Gowa Regency Government is responsible and obliged to ensure that the management of the Minasa Maupa Market is carried out optimally for the sake of mutual benefit, so that steps and improvement efforts must be taken immediately to maintain the competitiveness of the Minasa Maupa Market as a traditional market amid the rise of modern shopping centers.